PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, CAPITAL INTENSITY, DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK - Widiatno, Juliana G; Nataherwin, Nataherwin (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of conducting this research is to find out how profitability, company size, capital intensity and leverage affect the value of tax aggressiveness in non-cyclical sub-sector manufacturing companies listed on the Indonesia Stock Exchange during 2019-2021. The sample was selected by purposive sampling method to obtain valid company data results. In this study, 40 companies were found. Analysis data processing techniques using Partial Least Square in the SmartPLS 3.2.9 program and Microsoft Excel 2016. The results of the study found that profitability had a negative but not significant effect on tax aggressiveness, company size and capital intensity had a significant negative effect on tax aggressiveness, and leverage had a significant positive effect against tax aggressiveness.